Pengelolaan Wakaf Uang di Indonesia - Mustopa Kamal (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2021)
Cash waqf can play a role in supporting the overall development process, both in the development of human resources, as well as in economic and social development. The development of cash waqf has a strategic economic value. Through cash waqf, waqf assets in the form of vacant land can be utilized by building buildings or business facilities. Cash waqf has a positive effect on the economic empowerment of the community, waqf funds can also help empower small businesses. In addition, cash waqf plays a very important role as one of the pillars of social development and the development of a prosperous society. The results of the cash waqf investment can be channeled to help the operational costs of educational institutions, health institutions and social institutions. This is where cash waqf plays a role as an alternative source of funding for programs to improve the welfare of the people.